Assessing the effects of a road surfacing cartel in Switzerland - Kai Hüschelrath; Nina Leheyda; Patrick Frank Ernst Beschorner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The paper assesses the impact of the detection of a hard-core cartel in the Swiss market for road surfacing on post-cartel competition. In addition to an investigation of supply-side factors, demand-side factors, and market prices, the paper also derives estimates of the economic effects of the decision. The results indicate that the detection of the cartel may have led to short-term price reductions; however, the persistent collusion-friendly industry structure forecloses larger and durable gains for the customers.
Keywords: L41; K21; 330; Competition Policy; Evaluation; Cartels; Switzerland; Straßenbau; Kartell; Wettbewerbspolitik; Wohlfahrtseffekt; Schweiz